Fracture resistance of implant‐supported screw‐retained zirconia‐based molar restorations. Issue 9 (13th July 2016) - Honda, Junichi; Komine, Futoshi; Kamio, Shingo; Taguchi, Kohei; Blatz, Markus B.; Matsumura, Hideo
Abstract: Objectives: The objective of this in vitro study was to investigate fracture loads of screw‐retained zirconia‐based molar restorations (hybrid abutment crown) fabricated with different restorative materials and designs. Material and methods: Forty‐four screw‐retained zirconia‐based molar restorations were fabricated on dental implants and divided into four groups ( n  =   11): porcelain‐layered zirconia‐based restorations (PLZ), indirect composite‐layered zirconia‐based restorations (ILZ), metal–ceramic restorations (MC), and monolithic zirconia restorations (MONO). The zirconia‐based restorations in the PLZ, ILZ, and MONO groups were adhesively bonded on implant abutments with a dual‐polymerized resin material. All restorations were tightened on implant bodies with titanium screws and were tested for fracture resistance. The Kruskal–Wallis test and Steel–Dwass test were used to evaluate differences in fracture loads (α = 0.05). Results: As compared with the other groups, the MONO specimens had a significantly higher mean fracture resistance (7.54 kN); no significant differences were found among the PLZ (1.96 kN), ILZ (1.80 kN), and MC (1.45 kN) groups ( P  >   0.05). For the PLZ, ILZ, and MC groups, all specimens fractured within the layering materials. In contrast, the fracture mode for the MONO group was complete fracture of the restorations. Conclusions: All restorations withstood the masticatory forces. Fracture loads were significantly higher for screw‐retained implant‐supported monolithic zirconia restorations than for screw‐retained bilayered restorations. For the screw‐retained bilayered zirconia‐based restorations, the fracture resistance of ILZ restorations was comparable to that of PLZ restorations and MC restorations.